Association between dietary anthocyanidins intake and depression among US adults: a cross-sectional study (NHANES, 2007–2010 and 2017–2018) - Chen, Wen-li; Zhao, Jing (BMC psychiatry, 2023)
Anthocyanidins encompass a diverse array of compounds that possess notable anti-inflammatory and antioxidant properties with pharmacological activity. However, the correlation between the consumption of anthocyanidins through diet and its impact on depression has yet to be investigated. This study utilized the Food and Nutrient Database for Dietary Studies (FNDDS) expanded flavonoid intake database, as well as data from the National Health and Nutrition Examination Survey (NHANES) from the years 2007 to 2010 and 2017 to 2018. The analysis of the collected data was conducted in R, following the guidelines outlined in the official NHANES user guide "Stratified Multi-stage Probability Sampling". Three different models were developed using logistic regression to assess the protective effects of T3 (representing the highest intake of anthocyanidins) against depression. Additionally, the study aimed to investigate whether there existed a non-linear relationship between the dietary intake of anthocyanidins and the prevalence of depression by employing restricted cubic spline (RCS) analysis. A total of 6,845 eligible participants were included in this cross-sectional study, with their data appropriately weighted to represent a population of 89.8 million people in the United States of America. The results demonstrated that individuals diagnosed with depression had a significantly lower dietary intake of anthocyanidins compared to those without depression (P < 0.0001). Moreover, significant differences were observed among different participant groups regarding socioeconomic status and the presence of chronic physical illnesses (such as hypertension, glucose status, and chronic kidney disease risk, etc.) (P < 0.05). After adjustment for covariates, participants with the highest intake of anthocyanins (T3) demonstrated a significantly reduced risk of depression [OR = 0.67, 95%CI: (0.48-0.95), (P = 0.02]. Furthermore, the RCS analysis revealed a significant linear relationship between dietary anthocyanidin intake and depression (P for non-linear = 0.5876). Our findings reveal a negative association between dietary anthocyanidin intake and depression.